Identifying Factors Enhancing and Promoting Marital Satisfaction in a Healthy and Stable Marriage: A Qualitative Study Based on Grounded Theory - Talat Ahangar; Ahmad Borjali; Mahdi Davaee (روانشناسی بالینی و شخصیت, 2024)
Introduction: Marital satisfaction is a key indicator of the strength and effectiveness of the family system. The health of a family relies on the presence of a nurturing and evolving relationship; thus, marital satisfaction is essential for establishing a healthy and stable marriage. The present study was conducted to identify the factors that affect marital satisfaction.Method: The present study employed a qualitative, data-driven approach. The study population consisted of premarital counseling specialists who had been professionally active in Tehran in 2021 and had a minimum of five years of counseling experience. A total of 20 specialists participated in the present study. Participants were selected using purposive and accessible sampling methods. The primary tool used in the current study was semi-structured interviews. The analysis of the interviews was conducted using a categorization (coding) method.Results: Data analysis resulted in the identification of 25 open codes, 6 central codes, and a selected code of "marital satisfaction and a healthy, stable marriage." The analysis of the findings revealed that various factors contribute to marital satisfaction. Personality traits serve as reinforcing factors, while satisfying basic needs and strengthening communication skills act as enhancing factors. The results of the study indicate that personality traits—such as emotional stability, high self-confidence, responsibility, flexibility, and moral conscience—along with the fulfillment of basic needs (including the need for love and respect, personal growth, recognition, deep sexual relationships, and physical affection) and the enhancement of communication skills (such as conversational abilities, conflict resolution, interpersonal relationships, empathy, and stress management) significantly contribute to marital satisfaction. The outcomes of the study have been observed at three levels: individual (mental health), couple (adaptation, relationship stability, and reduction of psychological stress), and social (prevention of emotional and legal divorce).Discussion and conclusion: Identifying the factors that enhance and promote marital satisfaction provides valuable insights for counselors and psychologists. This knowledge can assist them in guiding individuals seeking marriage counseling, fostering stable marriages, and mitigating potential harms, as suggested by experts in the Iranian context.